PEMBERIAN JUS SIRSAK (Annona muricata Linn) TERHADAP KADAR ASAM URAT DARAH PADA PASIEN GOUT ARTHRITIS DI WILAYAH KERJA PUSKESMAS KOTOBANGON KOTAMOBAGU TIMUR - Irza Nanda Ranti; Vera T Harikedua; Nonce N Legi; Rudolf Boyke Purba; Siti L Dilapanga (Jurnal GIZIDO, 2022)
ABSTRACT Gout is an arthritis disease caused by abnormal purine metabolism which is characterized by increased levels of uric acid in the blood. The body parts that are often affected by gout arthritis are the joints of the fingers, knees, ankles, and toes. This study aims to determine the administration of soursop juice (Annona muricata Linn) on blood uric acid levels in gout arthritis patients in working area of Kotobangon Public Health Center, East Kotamobagu. This type of research is quantitative with a quasi-experimental design, pretest and posttest treatment. The study was conducted in the working area of the Kotobangon Public Health Center, East Kotamobagu in January – February 2021. The sample consisted of 33 people. The data collected were the characteristic of the respondents and examination of blood uric acid levels before and after administration of soursop juice. The statistical test used to distinguish blood uric acid levels before and after administration of soursop juice was the Paired Sample T Test. Blood uric acid levels before administration of soursop juice were the lowest 6,0 mg/dL and highest 8,3 mg/dL. Blood uric acid levels after administration of soursop juice were the lowest 3,0 mg/dL and highest 7,3 mg/dL. Decrease in blood uric acid levels by 32 people and an increase in blood uric acid levels by 1 person. The results of the analysis showed that there were differences in blood blood uric acid levels in patients with gout arthritis before and after administration of soursop juice and the average decrease in blood uric acid levels was 2,77 mg/dL. The Paired Sample T Test was carried out with p value = 0,000, because p = <0,05, then Ha was accepted. Keyword : Gout Arthritis, Blood Uric Acid Levels, Soursop Juice ABSTRAK Gout adalah salah satu penyakit arthritis yang disebabkan oleh metabolisme abnormal purin yang ditandai dengan meningkatnya kadar asam urat dalam darah. Bagian tubuh yang sering terserang gout arthritis adalah sendi jari tangan, lutut, pergelangan kaki, dan jari kaki. Penelitian ini bertujuan untuk mengetahui pemberian jus sirsak (Annona muricata Linn) terhadap kadar asam urat darah pada pasien gout arthritis di wilayah kerja Puskesmas Kotobangon Kotamobagu Timur. Jenis penelitian adalah kuantitatif dengan desain eksperimen semu, pretest dan posttest treatment. Penelitian dilakukan di wilayah kerja Puskesmas Kotobangon Kotamobagu Timur pada bulan Januari – Februari 2021. Sampel ada 33 orang. Data yang dikumpulkan adalah karakteristik responden dan pemeriksaan kadar asam urat darah sebelum dan sesudah pemberian jus sirsak. Uji statistik yang digunakan untuk membedakan kadar asam urat darah sebelum dan sesudah pemberian jus sirsak adalah Paired Sample T Test Kadar asam urat darah sebelum pemberian jus sirsak yaitu terendah 6,0 mg/dL dan tertinggi 8,3 mg/dL. Kadar asam urat darah sesudah pemberian jus sirsak yaitu terendah 3,0 mg/dL dan tertinggi 7,3 mg/dL. Penurunan kadar asam urat darah sebanyak 32 orang dan kenaikan kadar asam urat darah sebanyak 1 orang. Hasil analisis ada perbedaan kadar asam urat darah pada pasien gout arthtiris sebelum dan sesudah pemberian jus sirsak dan rata-rata penurunan kadar asam urat darah yaitu 2,77 mg/dL. Dilakukan Paired Sample T Test didapat nilai p = 0,000, karena nilai p = <0,05, maka Ha dapat diterima. Kata Kunci : Gout Arthritis, Kadar Asam Urat Darah, Jus Sirsak